An update of anthropogenic CO2 storage rates in the western South Atlantic and the role of Antarctic Bottom Water - Ríos, Aida F.; Velo, A.; Pardo, Paula C.; Hoppema, Mario; Pérez, Fiz F. (2011)
Póster presentado al congreso: GEO-CARBON CONFERENCE: CARBON IN A CHANGING WORLD, 24-26 OCTOBER 2011, ROMA.-- Proyecto Carbochange Re-evaluation of the CANT storage rates in the western South Atlantic and the role of the AABW using quality and quantity carbon measurements